José Nicolás de AZARA, «Primera Memoria», ed. María Dolores Gimeno Puyol, Zaragoza, Institución «Fernando el Católico», 245 págs. - López Souto, Noelia (Cuadernos de Estudios del Siglo XVIII, 2015)
SIN RESUMEN